Humanitarian response coordination architecture in Bangladesh Rohingya refugee crisis operation: practice, challenges and prospects - Ahmed, Khaled Masud (BRAC University, 2019)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2018.